Championing Olympic Excellence: A Bibliometric Analysis of Biomechanics Impacting Tennis Performance on the World Stage - Kumar, Sunil; Das, Ratna (Physical Education Theory and Methodology, 2024)
Objectives. The study aims to comprehensively analyze the existing literature on the relationship between biomechanics and tennis performance, with a particular focus on enhancing Olympic accomplishment. Materials and methods. Scopus was used to search three fields in each record: (1) Author’s name, (2) Journal Name where the paper was published, (3) Total citations. Bibliometric analysis was employed as a component of the analysis. To obtain a comprehensive and accurate understanding, the data was analyzed and interpreted using several methods of data triangulation. VOSviewer software was appliedto generate distance-based co-occurrence maps for bibliometric analysis and synthesis. The terms extracted from keywords, titles, and abstracts were categorized and organized based on their level of interconnectedness. The keywords “Biomechanics” and “tennis performance” are commonly employed in the study, and their meanings are often interpreted in different settings. The search yielded 240 papers and 6137 citations, which were used in the study conducted between 2000 and 2024. Results. The study’s findings identified “key authors, countries, and subject areas” contributing to thefield of biomechanics research in tennis, emphasizing interdisciplinary collaboration and future research directions. Conclusions. In conclusion, the study provides a foundation for continued research and innovation in championing Olympic excellence through biomechanics research in tennis.